The Song of Songs. A proposal the structural reading (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
In the criticism of the Song of Songs there is no agreement on the structural problem of the book. Theories are divided into those advocating a fragmentary against others who see a unitary character of poems. The study attempts to revise this problems and propose that the Song of Songs is a loose collection of poems that a compiler gathered and tried to give some order, incorporating the adjuration of 2, 7; 3,5; 5,8; 8,4 as refrain with articulate function, such that the adjuration was set as milestone dividing between  large blocks poetic that interrelate by a common theme or other resource or literary technique  thus configuring a structural arrangement of the whole book.
Keywords: Song of Songs; structure; literary analysis; adjuration